Silicon foam in the prevention of pressure injuries by the PFF2 (N95) mask in the Coronavirus pandemic (Research, Society and Development, 2021)
Objectives: Describe changes in skin integrity related to the use of a mask with filter part - PFF2, type N95 and describe preventive action of polyurethane foam coated with adhesive silicone. Methodology: qualitative observational study of the type of case reports. Data collected in October 2020 in four evaluations, with two participating nurses, one black and one white, both working on the front line of the COVID-19 pandemic. Results: With the implementation of high-tech foam composed of polyurethane and coated with adhesive silicone in the pressure areas exerted by the N95 mask, as a measure of pressure injury prevention, it was possible to observe in the clinical examination of the skin, the absence of erythema in the areas bony prominence of the face (nasal hump and malar regions), improvement of the skin microclimate (temperature and humidity), in addition to the absence of pain and burning sensation when in the absence of foam to relieve pressure. Conclusion: The polyurethane foam coated with adhesive silicone seems to control the risk factors - pressure, friction, shear, alteration of microclimate, in addition to pain and burning, referred to in areas of contact with the mask. However, more robust clinical studies with a larger number of participants are recommended for consensus on the best preventive method. It is emphasized that pressure relief every 2 hours is still the most recommended method in the world literature to maintain perfusion and tissue nutrition.